2004
DOI: 10.1179/108331904225007069
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Transcutaneous Electrical Nerve Stimulation for Osteoarthritis of the Lower Extremities: a Meta-analysis

Abstract: Although transcutaneous electrical nerve stimulation is commonly used to treat the pain of osteoarthritis, the effectiveness of this type of stimulation for pain relief remains controversial. This review found statistically significant results favouring conventional and acupuncture-like stimulation for pain relief and stiffness relief. Mixed stimulation was effective in reducing knee pain but had less effect on hip pain. Burst nerve stimulation resulted in statistically significant relief of knee stiffness and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 40 publications
0
8
0
2
Order By: Relevance
“…According to Rushton ( 30 ), TENS is one of the main therapeutic electrical currents used in acute and chronic pain conditions. This treatment has been used extensively in healthcare centers for the symptomatic management of acute and chronic pain of benign origin, and also in the palliative care of pain caused by metastatic bone diseases and neoplasms ( 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…According to Rushton ( 30 ), TENS is one of the main therapeutic electrical currents used in acute and chronic pain conditions. This treatment has been used extensively in healthcare centers for the symptomatic management of acute and chronic pain of benign origin, and also in the palliative care of pain caused by metastatic bone diseases and neoplasms ( 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…TENS is a method of electrical stimulation which primarily aims to provide a degree of symptomatic pain relief by exciting sensory nerves, which stimulate either the pain-gate mechanism and/or the opioid system 4 ) . Several systematic reviews have shown that TENS is one of the recommended treatments for pain relief in some patients with knee OA 5 , 6 , 7 ) . However, a previous study showed that there were no significant differences in performance measures between active TENS and placebo TENS 8 ) .…”
Section: Introductionmentioning
confidence: 99%
“…Електродите са поставени върху кожата в областта на болката. Методиката купира в значителна степен острата и хроничната болка, особено в краткосрочен план (първите 2-4 седмици от терапията) [15,16].…”
unclassified
“…Въпреки че не са наблюдавани сериозни странични реакции, някои кожни заболявания и наличието на пейсмейкър, дефибрилатор, инфузионни помпи са контраиндикации за прилагането на ТЕНС [15]. OARSI не препоръчва употребата на ТЕНС при ОА поради липсата на убедителни доказателства за нейната ефикасност [17].…”
unclassified
See 1 more Smart Citation